Nanoplastics and fungi: exploring dual roles in degradation and pathogenicity - Ma, Yuanyuan; Zhou, Yifan; Zheng, Dongnan; Bu, Wenxia; Wang, Fengxu; Zhao, Xinyuan; Xue, Peng (Frontiers in Microbiology, 2025)
Plastic pollution, particularly in the form of nanoplastics, represents a growing global environmental crisis with profound impacts on ecosystems and human health. This review investigates the multifaceted interactions between fungi and nanoplastics, highlighting fungi’s dual role in both the degradation of plastics and their potential pathogenicity. Fungi possess specialized enzymatic pathways, which empower them to effectively break down a variety of plastic materials, leading to innovative bioremediation approaches. However, the omnipresence of nanoplastics in the environment poses significant challenges, as they can adversely affect fungal physiology, altering metabolic processes, enhancing virulence, and potentially contributing to antifungal resistance. This review examines the mechanisms through which different fungal species degrade specific plastics while emphasizing the influence of nanoplastics on fungal metabolic pathways and collective community dynamics. It explores the adaptations fungi may exhibit in response to nanoplastic exposure, including changes in enzymatic activity and resistance mechanisms. Additionally, the review addresses the implications of nanoplastic exposure for the pathogenicity of fungi, particularly concerning their interactions with human hosts and resistance to antifungal treatments. By providing a thorough analysis of the current understanding of nanoplastics and fungi, this review calls for urgent research into the ecological consequences of these interactions and the potential for increasing antifungal resistance. Ultimately, this work aims to inform effective strategies for mitigating the dual threats of plastic pollution and fungal-related health issues.